กลยุทธ์การนิเทศแบบร่วมพัฒนาวิชาชีพของครูโรงเรียนมัธยมศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษา เขต 1 - สายเพ็ชร สิรดา; สุดรุ่ง จุไรรัตน์ (An Online Journal of Education, 2018)
The objectives of the research were 1) to study current and desirable state; 2) to arrange needs and analyze the strengths, weaknesses, opportunities and threats; 3) to purpose strategies professional cooperative professional development of secondary school teachers under the secondary educational service area office 1. The research instrument was questionnaires. The samples were 372 secondary school teachers in 67 schools under the secondary educational service area office 1. The data were analyzed by frequency, percentage, mean, standard deviation, PNI modified technique and content analysis. The findings were: The overall of current states was at the moderate level. Considering to each fields were found that the planning stages are at the highest level, the overall of desirable state was at the highest level. The average of co-planning stage was at the high level. The overview of PNI modified index value was 0.35. Sequencing by the emphasis point started from the supervision, giving feedback and co-planning. And 40 strengths, 30 weaknesses, 13 opportunities, and 21 threats. Strategies consist of 4 main primary strategies: the first is to develop secondary school teachers to plan professional development together. The second is to encourages teachers to develop the supervision. The third is to forces teachers to share their knowledge together. The fourth is to reinforce teachers to develop an innovation altogether.